The Effect Of Instagram Social Media Use On The Self-Healed Ability Of Students Of The University Of North Sumatera - All rizky ramadhan siregar; Andre Genesa Harahap; Anugerah Zebua; Natalia Syafitri Br Marpaung (Program Pascasarjana UIN Sumatera Utara, 2024)
This research is entitled